A STUDY OF UNCOATED AND COATED UREA CRYSTALS DISSOLUTION IN STIRRED VESSEL - M. H. Ismayanda; M. Zakaria (Dept. of Chemical Engineering, Diponegoro University, 2004)
An immersing and spray coating process has been developed for the continous production of tapioca starch and silica coated urea. The coating thicness and quality of coated urea was produced in a laboratory-scale unit. The dissolution rates of urea uncoated and coated urea crystals were studied in a stirred vessel. Coated urea crystals genarally shows low dissolution rates compared to uncoated for all coating materials. The effect of coating was best with tapoca starch and silica combination baked at 70oC. This cating material of tapioca starch coating urea the dissolution time was in the range of 300 to 360 second mass transfer coefficient in the range of between 3.63 x 10-6 to 2.91 x 10-3 cm 2/s. And for the silica coated urea coating material, the dissolution time was in the range of 300 to 380 second. mass coefficient in the ranger of 1.65 x 10-2 to 3.30 x 10-2 cm/s.and diffusion coefficient in the ranger of 3.57 x 10-6 to 3.30 x30 x 10-3 cm 2/s. The dissolution rangers from about 87% for a product containing 10.5 % tapioca starch to the dissolution range of about 85% for a product containing 9.5% silicaKeywords : urea crystals, Coating, dissolution, stirred vessel